Pelaksanaan Nikah Muhalil di Kecamatan Peranap Kabupaten Indragiri Hulu - Utami, Lisa Putri; Ismi, Hayatul; Hasanah, Ulfia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Nikah muhalil is a man who married a woman who was in triple divorce with the aim that the first man could come back with him. In this marriage muhalil, the problem arises when the engineering process occurs when the former husband looking for another man to marry his wife by stating the requirement is that the man who married his wife and then menceraikanya. The purpose of writing this thesis, namely; First, Implementation of marriage muhalil in Peranap District Indragiri Hulu Regency, Second, the factors causing the happening of marriage muhalil in Permanap District Indragiri Hulu Regency, Third, The impact of the happening of marriage muhalil in District Peranap.This type of research can be classified in the type of sociological juridical research, because in this study the authors directly conduct research on the location or place studied in order to provide a complete and clear picture of the problem under study. This research was conducted in Kecamatan Peranap of Indragiri Hulu Regency, while the population and sample were all parties related to the problem studied in this research, data source used, primary data, secondary data, and tertiary data, data collecting technique in this research with Interviews and literature study.From the results of research problems there are three main things that can be concluded. First, Nikah muhalil only to justify a woman who has been divorced three to be married back by her ex-husband. Secondly, the factors of the happening of marriage muhalil in Peranap District Indragiri Hulu regency like, the desire of married couples back with ex-spouses, religious factors, educational factors, economic factors, the lack of socialization of the relevant agencies, Third, the impact of the occurrence of marriage muhalil ie, Impact on the parties, impact on children, impact on marriage after marriage muhalil, impact on the environment. Suggestion Writer, First, For the government of Sub-District Peranap Indragiri Hulu need to socialize about marriage especially about this marriage muhalil and problem in it, Second, For those who carry out marriage muhalil expected to understand about purpose of real marriage and also for muhalil which justifies woman Have been denied three do not just get married to expect some money,Third, For religious leaders should explore the science of marriage law in Indonesia in order to understand the marriage and divorce procedures. Keywords: Implementation - Nikah Muhalil - District Peranap